General expression for tunable matching network efficiency in the case of complex impedances. Issue 5 (May 2015) - Freitas, Vitor; Arnould, Jean‐Daniel; Ferrari, Philippe
ABSTRACT: The design of matching networks is generally based on lossless devices, hence rendering difficult to anticipate their performance when both impedances are complex. To be more predictive in terms of insertion loss and matching impedance coverage, a rigorous method is proposed for the first time to calculate the efficiency of a tunable matching network based on the quality factor of its components, with source and load complex impedances. The method allows optimizing the topology of the matching network, depending on the location of the source and loading impedances in the Smith chart. It is the first time to our knowledge that a complete analytical formulas is given to predict the matching network's efficiency in function of available components quality factors in the case of source and load complex impedance. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1160–1166, 2014